Blau syndrome NOD2 mutations result in loss of NOD2 cross-regulatory function - Mao, Liming; Dhar, Atika; Meng, Guangxun; Fuss, Ivan; Montgomery-Recht, Kim; Yang, Zhiqiong; Xu, Qiuyun; Kitani, Atsushi; Strober, Warren (Frontiers in Immunology, 2022)
Mutations in the nucleotide binding domain of the CARD15 (NOD2) gene underlie the granulomatous inflammation characterizing Blau syndrome (BS). In studies probing the mechanism of this inflammation we show here that NOD2 plasmids expressing various Blau mutations in HEK293 cells result in reduced NOD2 activation of RIPK2 and correspondingly reduced NOD2 activation of NF-B. These in vitro studies of NOD2 signaling were accompanied in vivo studies showing that BS-NOD2 also exhibit defects in cross-regulation of innate responses underlying inflammation. Thus, whereas over-expressed intact NOD2 suppresses TNBS-colitis, over-expressed BS-NOD2 does not; in addition, whereas administration of NOD2 ligand (muramyl dipeptide, MDP) suppresses DSS-colitis in Wild Type (WT) mice it fails to do so in homozygous or heterozygous mice bearing a NOD2 Blau mutation. Similarly, mice bearing a Blau mutation exhibit enhanced anti-collagen antibody-induced arthritis. The basis of such cross-regulatory failure was revealed in studies showing that MDP-stimulated cells bearing BS-NOD2 exhibit a reduced capacity to signal via RIPK2 as well as a reduced capacity to up-regulate IRF4, a factor shown previously to mediate NOD2 suppression of NF-B activation. Indeed, TLR-stimulated cells bearing a Blau mutation exhibited enhanced in vitro cytokine responses that are quieted by lentivirus transduction of IRF4. In addition, enhanced anti-collagen-induced joint inflammation in mice bearing a Blau mutation was accompanied by reduced IRF4 expression in inflamed joint tissue and IRF4 expression was reduced in MDP-stimulated cells from BS patients. Thus, inflammation characterizing Blau syndrome are caused, at least in part, by faulty canonical signaling and reduce IRF4-mediated cross-regulation.